Differences between early and late involvement of palliative home care in oncology care: A focus group study with palliative home care teams. (July 2018) - Dhollander, Naomi; Deliens, Luc; Van Belle, Simon; De Vleminck, Aline; Pardon, Koen
Background: To date, no randomised controlled trials on the integration of specialised palliative home care into oncology care have been identified. Information on whether existing models of integrated care are applicable to the home care system and how working procedures and skills of the palliative care teams might require adaptation is missing. Aim: To gain insight into differences between early and late involvement and the effect on existing working procedures and skills as perceived by palliative home care teams. Design: Qualitative study – focus group interviews. Setting/participants: Six palliative home care teams in Flanders, Belgium. Participants included physicians, nurses and psychologists. Results: Differences were found concerning (1) reasons for initiation, (2) planning of care process, (3) focus on future goals versus problems, (4) opportunity to provide holistic care, (5) empowerment of patients and (6) empowerment of professional caregivers. A shift from a medical approach to a more holistic approach is the most noticeable. Being involved earlier also results in a more structured follow-up and in empowering the patient to be part of the decision-making process. Early involvement creates the need for transmural collaboration, which leads to the teams taking on more supporting and coordinating tasks. Discussion: Being involved earlier leads to different tasks and working procedures and to the need for transmural collaboration. Future research might focus on the development of an intervention model for the early integration of palliative home care into oncology care. To develop this model, components of existing models might need to be adapted or extended.